The evolution of the mantle source beneath Mt. Etna (Sicily, Italy): from the 600 ka tholeiites to the recent trachybasaltic magmas. Issue 3 (11th February 2020) - Casetta, Federico; Giacomoni, Pier Paolo; Ferlito, Carmelo; Bonadiman, Costanza; Coltorti, Massimo
ABSTRACT: The spatial/temporal proximity of Mt. Etna to the Hyblean Plateau and the Aeolian slab makes the discussion on the nature of its mantle source/s extremely controversial. In this study, a detailed geochemical overview of the entire Mt. Etna evolutionary sequence and a comparison with the magmatism of the Hyblean Plateau was proposed to: (i) simulate the composition of Mt. Etna tholeiitic to alkaline primitive magmas in equilibrium with a fertile mantle source; (ii) model the nature, composition and evolution of the mantle source from the tholeiitic stage (600 ka) to present magmatism. According to our simulations, two amphibole + phlogopite-bearing spinel lherzolite sources are able to explain the wide range of Etnean primary magmas. The enrichment in LILE, 87 Sr/ 86 Sr, Rb and H2 O of the magmas emitted after 1971 (but also discontinuously generated in both historic and prehistoric times) are caused by different melting proportions of amphibole and phlogopite in a modally and compositionally homogeneous mantle domain, with melting degrees analogous to those required to produce magmas erupted prior to 1971. The behaviour of the hydrous phases during melting could be ascribed to a variable H2 O/CO2 activity in the mantle source, in turn related to the heat/fluxes supply from the asthenospheric upwelling beneath Mt. Etna. All these considerations, strengthened by numerical models, are then merged to review the complex Pliocene/Lower Pleistocene to present day's geodynamic evolution of eastern Sicily.